Development of Pop-Up Book Media to Teach Vocabulary for Mental Retardation Special School - Ainaul Mardliyah; Widiarini Widiarini; Ahmad Saifudin; Siti Rofi'ah (Journal of Development Research, 2022)
This research was carried out based on the results of observations on mentally retarded students at SLB Jatiwiratama Selopuro in the vocabulary subject. This study aims to develop learning media in the form of pop-up book and find out how the level of feasibility of the media. This research was conducted on mentally retarded children at special school. The research method used is Research and Development (R & D) which adopted from Borg and Gall where researchers take 4 stages of the existing 10 stages. The stages include (1) Need analysis, (2) Product development, (3) Product testing, (4) Product revision. Determination of eligibility is done by validate the learning experts, and media experts. After that, the researcher do product testing. Research and development produces pop-up book media that are suitable for use based on the assessment of (1) Media expert validators get an assessment of 95.5% (2) Learning expert validators received a 9% rating. Assessment of student responses gets an assessment percentage of 91.5% which is means that the media can be accepted by students. The reason for choosing this research is because the development of pop-up book media for mentally retarded children has never been researched before.